(untitled) (Journal of Shaheed Suhrawardy Medical College, 2013)
Halitosis is known as bad breath that emanates from the oral cavity either intra-oral and/or extra-oral origins with different nomenclature such as oral malodor, foetor ex ore, bad breath, foul smell or in Bengali durgondha. Fifty percent of people worldwide view themselves as having halitosis, with (85.0-90.0%) of the etiology being intra-oral. Oral causes include basically tongue coating and other various causes like tooth decay, periodontitis, chronic gingivitis, oral infections, pericoronitis, calculus deposition, oral mucosal ulceration (bacterial and/or fungal), impacted food particles, orthodontic problems and poor oral hygiene practice. These sorts of foul smell of the oral cavity most often results from the bacterial degradation of oral organic substrates as volatile sulfur compounds (VSC). The source of halitosis may be related both to oral and systemic condition, but majority of cases are commonly related to oral factors. So far knowledge goes there have been a few studies evaluating the prevalence of bad mouth breath (BMB) in general population. The aim of this reviews are the classification of halitosis, assessment, diagnosis, intra-oral and systemic contributing factors, treatment, management and clinical application. DOI: http://dx.doi.org/10.3329/jssmc.v5i2.20767 J Shaheed Suhrawardy Med Coll 2013;5(2):106-110